2020
DOI: 10.1177/1403494820973096
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, mental health and substance use of anabolic steroid users: a population-based study on young individuals

Abstract: Aims: The use of anabolic androgen steroids to enhance performance is not a modern phenomenon. However, the majority of today’s anabolic androgen steroid users are not competitive athletes, but individuals who want to look leaner and muscular. This study aimed to examine the prevalence of anabolic androgen steroid use among young individuals and assess whether their mental health, lifestyle and substance use differ from non-anabolic androgen steroid users. Methods: A population-based study conducted in seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 26 publications
2
22
0
8
Order By: Relevance
“…Of the 13 included studies, 4 are case studies [9 ▪▪ ,12–14], 4 are cross-sectional studies [15 ▪ –18 ▪ ], and two are meta-analyses of randomized controlled trials (RCTs) [19 ▪▪ ,20 ▪▪ ]. Additionally, two are systematic reviews on the effects of androgen therapy on aggression in transgender men [21 ▪ ] and the side effects of nandrolone decanoate [22], whereas one is a double-blind placebo-controlled RCT [23 ▪ ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 13 included studies, 4 are case studies [9 ▪▪ ,12–14], 4 are cross-sectional studies [15 ▪ –18 ▪ ], and two are meta-analyses of randomized controlled trials (RCTs) [19 ▪▪ ,20 ▪▪ ]. Additionally, two are systematic reviews on the effects of androgen therapy on aggression in transgender men [21 ▪ ] and the side effects of nandrolone decanoate [22], whereas one is a double-blind placebo-controlled RCT [23 ▪ ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies included a total of 12 556 persons constituting 6661 men, 5154 women, 664 transgender men, and ‘other’ ( n = 77). Only four studies [16 ▪ ,17 ▪ ,20 ▪▪ ,22] sampled women. Androgen abuse duration ranged from a few months [9 ▪▪ ] to 11 years [14] in the case reports, 1.33 [16 ▪ ] to 14.1 [18 ▪ ] years in the cross-sectional studies [15 ▪ ,17 ▪ ], one-time to 28 weeks in the meta-analyses of RCTs [19 ▪▪ ,20 ▪▪ ], and a one-time administration in the RCT [23 ▪ ].…”
Section: Resultsmentioning
confidence: 99%
“…Also of note, it has been reported that among AAS users who sought help to quit AAS use, most did so as a result of mental health problems, with depression and anxiety being the most prominent effects described (Havnes et al, 2019). It has also been reported that AAS users are more prone to suicide or suicidal ideation than nonusers (Gestsdottir et al, 2021;Patel et al, 2021;Petersson et al, 2006;Thiblin et al, 1999), and that this risk increases if personality disorders are present (Borjesson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mental health issues are a concern among AAS users. AAS users are reported to have more anxiety, depression, and anger issues than non-AAS users (Ip et al 2011;Gestsdottir et al 2020). Further, AAS-dependent users have higher rates of anxiety, depression, conduct disorder, body dysmorphic disorder, and muscle dysmorphia compared to non-AAS-dependent users or non-AAS users (Ip et al 2012a;Kanayama et al 2009a).…”
Section: Applications To Other Areas Of Public Healthmentioning
confidence: 98%
“…This also held true for older AAS users (40 years old), where rates of an anxiety disorder were over four times greater among AAS users than non-AAS users (12.0% vs. 2.6%, p¼0.046) (Ip et al 2015). Gestdottier and colleagues reported AAS users were more likely to meet criteria for anxiety (14.6% vs. 12.7%, p<0.001), depression (27.8% vs. 24.8%, p¼0.002), and anger issues (11.0% vs. 8.9%, p<0.001) than non-AAS users (Gestsdottir et al 2020). Female AAS users had higher rates of bulimia nervosa (25.0% vs. 3.5%, p¼0.01) and attention-deficit/hyperactivity disorder (ADHD) (16.7% vs. 2.2%, p¼0.04) than female non-AAS users (Ip et al 2010).…”
Section: Effects On Mental Healthmentioning
confidence: 99%